SISTEM PELARASAN GITAR KLASIK LAMPUNG PEPADUN - Barnawi, Erizal; Hasyimkan, Hasyimkan; Hernanda, Agung Hero (IAIIG Cilacap, 2020)
Gitar Klasik Lampung or Peting Tunggal is an acculturation music between Portuguese music and Lampung music. The form of acculturation is the guitar instrument from Portuguese and lyrics, the tuning system, and grenek from Lampung Pepadun people's culture and intelligence. Gitar Klasik Lampung Pepadun is also known as a type of vocal instrument performance art which has long been an instrument of expression and a part of people's lives that are currently following the times.Until now, Gitar Klasik Lampung Pepadun has developed very rapidly due to the presence of indirect social media to promote this art. Finally, many young people have emerged to learn and show their expertise on Instagram and their personal Facebook. Already began to emerge sanggar's from the original village of Lampung who studied and became a pioneer of the Gitar Klasik Lampung Pepadun.Gitar Klasik Lampung Pepadun has a different tuning system than the standard guitar. The tuning system is called Stem Pal, Stem Kembang kacang, Stem Be, Stem sanak mewang, and Stem hawayang. Excerpts (tetti ') consist of tetti' pal, Tetti' kembang kacang, tetti' Stambul, tetti' Keroncong Pandan, tetti' Tiga serangkai, tetti' Las Bas, tetti' Sanak Mewang di Ejan, tetti' Sai Kris, Tetti 'Hawayang' and Sandung.